ANALYSIS OF COSTS AND INCOME OF COCONUT FARMING IN PANTAI LABU DISTRICT, DELI SERDANG REGENCY - Elwardi Hasibuan; Siska Yulianita; Irshad Ahmad Reshi (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2025)
This study aims to analyze the production costs, revenues, and income of coconut farming in Pantai Labu District, Deli Serdang Regency. This study uses a survey method with a quantitative descriptive approach. The data used consists of primary data obtained through direct interviews with farmers using questionnaires, as well as secondary data from related agencies. Data analysis was carried out using cost, revenue, and farm income analysis. The results of the study indicate that the total production costs of coconut farming are Rp 6,131,275 per year. The average production of coconuts produced by farmers is 22,015 coconuts with a selling price of Rp 1,200 per coconut, resulting in revenue of Rp 26,417,700 per year. The net income earned by farmers is Rp 20,286,425 per year. Based on the results of the study, coconut farming in Pantai Labu District is classified as profitable and feasible to be developed because the revenue obtained is greater than the production costs incurred. Therefore, efforts are needed to increase the efficiency of cost use and support from the government in the form of extension and price stabilization to improve farmer welfare.